Perspektif Keberlanjutan dalam Penggunaan Material Alam untuk Infrastruktur Wilayah Perkotaan - PLAMONIA, NICCO; Junizal, Farhan; Irawanto, Rony; Prasidha, I Nyoman Teguh; Firdaus, Yustisia (Jurnal Teknik Sipil, 2024)
Abstract Constructing a hotel have to include various facility. One of the many may a jogging track. We take the Aruss Hotel in Semarang, Central Java, as the case to be studied. The Hotel planned to use Ironwood as the material for the track due to its solid and resistant characteristics. However, using the wood material collectively adds more pressure to the rainforest. Therefore we propose to replace the Ironwood with andesite stone. The andesite material also has solid and resistant characteristics. We argue that materials usage should consider the sustainability aspect of materials and the Value for Money factor. Therefore, the objective of this article is to provide a perspective for decision-makers that includes the sustainability perspective and the VFM principle. We conducted two activities during the Research: (1) comparing the cost of both materials and (2) comparing the time consumed installing both materials. The analysis results are as follows: The cost of using andesite is 73% cheaper than Ironwood. We replaced the Ironwood with an andesite, which is proven to save IDR 307,031,041. Moreover, using the andesite only takes 13 working days, while Ironwood takes 36 days. We conclude that using andesite as the alternative to Ironwood has two advantages: (1) reducing the pressure on the natural forest, and (2) saving the construction cost.